Public Participation in Social Impact Assessment: Comparative Human Rights Legal Approaches in Malaysia and Indonesia - Suaree, Nur Atheefa Sufeena M; Uz Zaman, Muhamad Nafi (LAW REFORM, 2025)
The Social Impact Assessment (SIA) is a widely used tool, including in Malaysia and Indonesia, for determining the potential positive or negative impacts of development projects in areas close to communities. The main goal of an SIA is to mitigate negative impacts and protect affected communities. Public participation is a key element of the SIA process and is strictly adhered to as a means of protecting human rights. Through doctrinal research utilising a qualitative methodology and comparative analysis of library resources, this paper aims to examine the implementation of human rights within the public participation mechanisms of these two countries. This fundamental right enables the public, particularly those affected, to contribute to the decision-making process. Both Malaysia and Indonesia share this objective, aligning with global efforts to uphold human rights in development contexts. However, in terms of SIA institutions and procedures, the two countries have distinct mechanisms. It can be concluded that both Indonesia and Malaysia have structured public participation as a multi-stage process within the SIA framework, albeit sometimes merely as a procedural formality. To uphold the dignity of affected communities, this paper recommends that Malaysia and Indonesia must move beyond procedural compliance and embrace genuine, rights-based engagement at every stage of development planning.